Reminder of an important clinical lesson: breast cancer metastasis to the parotid gland - Jakharia-Shah, Amisha (BMJ Case Rep, 2019)
A 59-year-old woman presented to an otolaryngology clinic with an 8-week history of a painless lump over her left parotid gland. Her medical history included an invasive ductal carcinoma (33 mm) and a ductal carcinoma in situ (70 mm) of the right breast, for which she had a mastectomy and various adjuvant therapies. The primary tumour presented 8 years prior to the metachronous metastasis. This patient was a non-smoker and had no significant family history. Post-superficial parotidectomy pathology revealed the parotid gland tumour to be oestrogen receptor-positive and HER2 receptor-positive, thus ruling out the initial differential diagnosis of a pleomorphic adenoma. A consequential total parotidectomy with a posterolateral neck dissection was performed with sparing of the facial nerve. The patient recovered well having only encountered a self-resolving salivary fistula. She portrayed no signs of facial nerve palsy and subsequent imaging scans showed no abnormalities.